Morphological adjustments to hydrologic correction works and erosion control in a Mediterranean fluvial system: Río Chico (Vélez Rubio, Almería). - Pérez-Cutillas, Pedro; Conesa-García, Carmelo; Sánchez-Gonzálvez, Miguel (Revista de Estudios Andaluces, 2015)
<span style="font-family: 'Calibri','sans-serif'; font-size: 12pt; mso-fareast-font-family: 'Times New Roman'; mso-bidi-font-family: Calibri; mso-ansi-language: EN-GB; mso-fareast-language: ES; mso-bidi-language: AR-SA;" lang="EN-GB">The Mediterranean fluvial systems, characterised by irregular and high intensity rainfall, are extremely vulnerable environments. These natural systems are altered by human activities, causing morphological adjustments and numerous, serious environmental problems in recent decades. A clear example of this is the river Chico, which has been submitted to an intense alteration, both hydrologic and morphologic. Dams and ripraps have been the constructions used most, although they have not always been effective, in many cases generating changes in the sedimentary flows and in the processes of erosion. On the contrary, the smaller-scale works carried out present a better integration in the riverbed, have performed well and have not provoked big local alterations. The absence or decrease of these works in the riverbed would yield a greater fluvial space, guaranteeing the recovery of the natural values.